Co0superparamagnetic Nanoparticles Stabilized by an Organic Layer Coating with Antimicrobial Activity - Venegas-Yazigi, D; Venegas-Yazigi, D (Royal Society of Chemistry, 2020)
Cobalt (Co) is one of the most promising materials in nanotechnology due to its superior magnetic properties. However, due to the high cytotoxicity of cobalt, the activity in biological systems has been little studied. In this work, we report the structural, morphological, and magnetic properties of cobalt nanoparticles stabilized with an organic layer (Co0@C-NPs) and its potential antimicrobial activity. The Co0@C-NPs were obtained from solvothermal conditions and characterized by X-ray powder diffraction, electronic microscopy, and magnetic measurements. The organic layer was analysed by thermogravimetric analysis, Scanning Electron Microscopy, Energy Dispersive Spectrometer, and Fourier Transform Infrared Spectroscopy. From the TEM image, an organic coating layer is observed around Co0where this coating prevents NPs from oxidation allowing it to remain stable until 400 °C. Surface composition studies by SEM/EDS allowed the identification of carbon, oxygen, and cobalt elements present in the organic layer. This result was corroborated later by FITR analysis. Preliminary antibacterial properties were also investigated, which showed that the cobalt nanoparticles are active againstStaphylococcus aureusafter 1 h of exposure. The superparamagnetic properties and organic coating Co0@C-NPs could be biocompatible with biological systems, but more research is needed to apply these nanoparticles in biomedical products. © The Royal Society of Chemistry 2020.